Improving Financial Technology-Based Financial Management for Noken Mama Papuan Artisans in Baliem Jayawijaya Valley - syarifah; Silviani Rumagit; Nanang Gunawan; Fayra Nabillah Azza; Tommi Hutasoit (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
This community service activity aims to enhance financial management literacy and the adoption of financial technology (fintech) among the Mama Papua Suara Hati Ibu noken craftsman group in the Baliem Valley, Jayawijaya. The main problems faced by partners are traditional financial record keeping, limited access to formal financial services, and low understanding of fintech applications. The implementation method is socialization, training, mentoring, and evaluation through pre-test and post-test. The results of the activity show a significant increase in knowledge and skills of partners in managing finances in a structured manner by utilizing the Qasir application as a digital recording medium, namely 60% where initially only 3 people understood financial technology, after the training, the number increased to 28 people. Supporting factors for this community service activity were the active role of all participants during the implementation, the partners' openness to problems faced, and the existence of clear duties and functions for partners, so that it was easy to coordinate the course of the training, as well as the support of the tribal chief regarding security during the activity. However, there were several obstacles during the implementation, including limited access to electricity, unstable internet, and tribal war during the activity, that required rescheduling and adding training time. The hope is that this activity will foster digital financial management literacy among partners, promote economic independence, and serve as a model for sustainable technology-based MSME empowerment in underserved and underserved regions (3T). Keywords: Qasir App, Financial Technology, Mama Papua, Noken, Underserved and Underserved MSMEs (3T)